In vitro cytotoxicity comparison of stingless bee propolis and cisplatin against ORL-48 and HGF / Ikmal Hisham Ismail ... [et al.] - Ismail, Ikmal Hisham; Saharuzaman, Syahmirul; Ahmad Naqiyuddin, Faatin ‘Afeefah; Bismelah, Amiyah; Khor, Goot Heah; Wan Ismail, Wan Iryani (Faculty of Dentistry, 2025)
Objectives: To assess the impact of Malaysian Heterotrigona itama (HI) propolis on the proliferation of oral squamous cell carcinoma cell lines (ORL-48) and Human Gingival Fibroblasts (HGF) through comparative treatment at different concentrations and time intervals. Method: The ORL-48 and HGF cell lines were treated with varying HI propolis and cisplatin concentrations. Subsequently, the 3-(4, 5dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay evaluated the in vitro cytotoxicity of HI propolis and cisplatin against ORL-48 and HGF cell lines. Result: This study discovered that HI propolis could inhibit the proliferation of ORL-48 cells in a concentration-dependent manner. From the increased treatment concentrations, the HI propolis administration to HGF cells demonstrated a proportional rise in the cell proliferation percentage of HGF cells. Nevertheless, cisplatin treatment significantly decreased the cell viability of ORL-48 cells with a half maximal inhibitory concentration (IC ) of 0.0036 mg/ml at 72 h (p < 0.05). Meanwhile, no significant reduction in cell viability was observed in HGF cells. 50 Conclusion: Propolis-based HI exhibited in vitro cytotoxic activity against human cancer cell lines while demonstrating lower cytotoxicity towards normal cells.